Senior High School Students’ Entrepreneurial Skills, Knowledge, and Competencies - Jambo, Joreme; Macalisang, Denmark; Calimpong, Michelle; Novida, Ligaya (Journal of Interdisciplinary Perspectives, 2025)
This study examined the entrepreneurial skills, knowledge, and competencies of Grade 12 students to identify strengths and areas for improvement. Using a descriptive survey research design, data were collected from a sample of Grade 12 students, and analyzed using weighted mean, standard deviation, frequency count, and percentage. Results showed that students demonstrated strong competencies in continuous learning, practical business skills, and risk management. However, they reported challenges in networking, presenting business plans, and financial literacy. The findings highlight the need for targeted interventions, such as mentorship programs and skill-based training, to enhance students' entrepreneurial readiness. Providing adequate support and resources can further empower students to navigate the demands of entrepreneurship effectively.